Students-Centered Engagement with English Language Teaching Using Project-Based Learning Model - Miftah Ikmal; Rahmawati Sukmaningrum; Sri Winarsih (ETERNAL (English Teaching Journal), 2023)
Abstract. This research aims to investigate student engagement in SCL (Student-Centered Learning) activities. The researcher focuses on four dimensions of engagement (cognitive engagement, behavioral engagement, emotional engagement, and social engagement). A review of related literature suggests that those four dimensions matter in conducting English learning studies. In addition, student engagement plays a vital role in the teaching and learning process. A qualitative descriptive study had used to observe 35 students. The research utilized a semi-structured interview with four students to give a brief explanation. The data analysis of this research presents four dimensions of engagement in the implementation of Project Based Learning (PjBL) as one of SCL in an English Language study. The result show that they engaged actively with the PjBL model. SCL's approach took part in their desire to adhere to learning activities. Furthermore, teachers as a facilitator make the learning process run dynamically. Accordingly, the findings of this research support the premise that student engagement optimizes learning and maximizes the learning outcome.